Intrinsic nature of chiral charge order in the kagome superconductor RbV₃Sb₅ - Shumiya, Nana (2022)
Superconductors with kagome lattices have been identified for over 40 years, with a superconducting transition temperature TC up to 7K. Recently, certain kagome superconductors have been found to exhibit an exotic charge order, which intertwines with superconductivity and persists to a temperature being one order of magnitude higher than TC. In this work, we use scanning tunneling microscopy (STM) to study the charge order in kagome superconductor RbV3Sb5. We observe both a 2×2 chiral charge order and nematic surface superlattices (predominantly 1×4). We find that the 2×2 charge order exhibits intrinsic chirality with magnetic field tunability. Defects can scatter electrons to introduce standing waves, which couple with the charge order to cause extrinsic effects. While the chiral charge order resembles that discovered in KV3Sb5, it further interacts with the nematic surface superlattices that are absent in KV3Sb5 but exist in CsV3Sb5.